A novel protocol to measure short sprint performance - Healy, R.; Norris, M.; Kenny, I. C.; Harrison, A. J. (Procedia Engineering, 2016)
This study assessed the validity of a novel protocol in the measurement of 5 and 10 m sprint time from standing and block starts. Sprint time was assessed using high speed video timing and a novel method which incorporated dual beam photocells synchronized with an optical measuring system. Team sport athletes and sprinters completed 10 m sprints from standing and block starts with both methods measuring sprint time concurrently. No significant differences were found between methods (p > 0.05) with a negligible mean bias (< 0.01 s). These results suggest that the novel method can accurately measure short sprint performance.